Modified marionette technique for uniportal video-assisted thoracic surgery: a case report - Sumitaka Yamanaka; Kensuke Adachi (Surgical Case Reports, 2019)
Abstract Background The current state of thoracoscopic technology allows less invasive surgical procedures and requires fewer ports and incisions. Totally video-assisted thoracic surgery with a single port has emerged as the least invasive thoracoscopic approach. However, uniportal video-assisted thoracic surgery brings about considerable difficulties, necessitating the development of skillful techniques as well as specific surgical devices. In such situations as dense pleural adhesion and anatomical abnormality, it may be more burdensome, necessitating the conversion to conventional multiportal video-assisted thoracic surgery or even to thoracotomy. To troubleshoot these situations, we herein propose the use of additional technique which could support to sustain the confident operative field for uniportal video-assisted thoracic surgery. This procedure also provides the same cosmetic outcomes as uniportal video-assisted thoracic surgery. Case presentation A previously healthy, 77-year-old female was referred to our hospital, with a lung adenocarcinoma measuring 28 mm in the right upper lobe. Uniportal video-assisted thoracoscopic surgery was planned to resect the tumor. During operation, we found the incomplete interlobar fissure between the upper and the middle lobe and the abnormal lobulation of the upper lobe. Therefore, the modified marionette technique was introduced to make the procedure safer and easier. This technique proposed herein consists of employing the untethered gripping forceps to retract the lung, not requiring additional traumatic trocars. The postoperative course was uneventful and the patient `was discharged in 1 week after a modified uniportal video-assisted thoracic surgery for the right upper lobectomy. Conclusions The modified marionette technique produced sufficient operative views to attain uniportal video-assisted thoracic surgery safely in this case, rendering operative conversion unnecessary.